Análisis retrospectivo del terremoto de Limón del 22 de abril de 1991 (Mw 7,7) y de la actividad sísmica disparada en las fallas Ayil, Pacuare, Atirro, División y Navarro - Montero-Pohly, Walter (Universidad de Costa Rica, 2021)
A retrospective analysis of the April 22, 1991 Limón earthquake (Mw 7.7) and of its aftershock and triggered activity is performed using seismicity, seismotectonic and neotectonic data. The seismic rupture area is reviewed as well as inversion models that allow to obtain the focal mechanism, and seismic moment. Different studies confirm that the mainshock source was a low angle thrust fault dipping southwest located in the back-arc region of the Talamanca Cordillera. The fault overthrusts the Panama block over the Caribbean plate. The analysis of the triggered seismicity and its seismotectonics show that the right-lateral Ayil, Pacuare and Atirro faults and the División and Navarro left-lateral faults were reactivated by the Limón earthquake. These faults are located along the Central Costa Rica Deformed Belt and in the transition zone with the western border of the North Panama Deformed Belt.